DEVELOPMENT OF AUGMENTED REALITY AS A LEARNING MEDIA FOR SBDP IN CLASS V STUDENTS MIN 4 JEMBER - Ramadhan, Firman Aulia (Attadib: Journal of Elementary Education, 2023)
The existence of issues in the environment of arts and culture material learning activities using musical notation in primary schools is what spurred this research. Researchers created a learning medium based on the Android operating system because these learning activities did not receive positive feedback. 1) The development of augmented reality-based learning materials for fourth-grade elementary schools' arts and crafts classes that explore musical notes. 2) Another goal of this research is to ascertain how media experts and subject matter experts create learning media, and 3) how effective learning media implementation is. The research and development technique was employed in this study, and the end result is a product whose viability has been proven. (1) The design of instructional materials for augmented reality employing tools from Adobe Photoshop CC 2021, Adobe XD CC, Blender 3D, Unity 3D, Cubase 12 Pro, and Vuforia SDK (2) The results show that the Augmented Reality learning medium achieves 96.7% (in the small group) and 91.6% (in the big group), showing that it is very effective and well suited for usage as a learning medium. These findings led to the conclusion that this arts and crafts learning medium was effective and suitable for use as a teaching tool for elementary school fifth graders.Keywords: Learning Media, Augmented Reality, Music